2021
DOI: 10.1073/pnas.2111358118
|View full text |Cite
|
Sign up to set email alerts
|

The middle cingulate cortex and dorso-central insula: A mirror circuit encoding observation and execution of vitality forms

Abstract: Actions with identical goals can be executed in different ways (gentle, rude, vigorous, etc.), which D. N. Stern called vitality forms [D. N. Stern, Forms of Vitality Exploring Dynamic Experience in Psychology, Arts, Psychotherapy, and Development (2010)]. Vitality forms express the agent’s attitudes toward others. In a series of fMRI studies, we found that the dorso-central insula (DCI) is the region that is selectively active during both vitality form observation and execution. In one previous experiment, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The cingulate cortex is usually considered to be a part of the limbic system ( Rolls, 2019 ), which is associated with memory, sleep, emotions, and behavior. The previous study suggested that the middle cingulate cortex was strongly activated during both action observation and execution ( Di Cesare et al, 2021 ). The decreased activity in the middle cingulate cortex may reflect the underlying basis for the impairment of executive function and cognition in patients with chronic pontine infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The cingulate cortex is usually considered to be a part of the limbic system ( Rolls, 2019 ), which is associated with memory, sleep, emotions, and behavior. The previous study suggested that the middle cingulate cortex was strongly activated during both action observation and execution ( Di Cesare et al, 2021 ). The decreased activity in the middle cingulate cortex may reflect the underlying basis for the impairment of executive function and cognition in patients with chronic pontine infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The MCC and insula are anatomically connected and form a vitality form circuit, which plays a role in the expression of actions (e.g., gentle, rude etc.) (Cesare et al, 2021). Although the existing literature about the role of MCC in AUD is limited, based on prior findings it is possible that an alteration in response to stressful cues contribute to deviations from expression of normal vitality forms in persons with AUD.…”
Section: Differences In Insular Seed-based Resting State Functional C...mentioning
confidence: 99%
“…Participants performed two different tasks: observing a gentle or rude action and performing the same action. The results indicated that the MCC was strongly activated during action observation and execution, in addition to the insula ( Di Cesare et al, 2021a ). Besides, the neural bases of vitality forms should be incorporated into the larger MNS in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…It can also explain the difficulty of healthy children in recognizing the vitality forms of autistic children, that is, it is difficult for them to match the sensory modules of the motor kinematics observed in children with autism with their own brain processing and corresponding modules of vitality forms (see Figure 1 ). Di Cesare et al (2021a) suggest that besides the DCI, the middle cingulate cortex (MCC) is also strongly activated during action observation and execution. This new finding is involved with a new how-dimension of action, by using jerky movements as a control condition.…”
Section: Discussionmentioning
confidence: 99%